Proteome-wide changes in primary skin keratinocytes exposed to diesel particulate extract—A role for antioxidants in skin health. Issue 3 (September 2018) - Rajagopalan, Pavithra; Jain, Ankit P.; Nanjappa, Vishalakshi; Patel, Krishna; Mangalaparthi, Kiran K.; Babu, Niraj; Cavusoglu, Nükhet; Roy, Nita; Soeur, Jeremie; Breton, Lionel; Pandey, Akhilesh; Gowda, Harsha; et al.
Highlights: Chronic exposure to diesel particulate extract/ its vapor cause global proteomic alterations in primary skin keratinocytes. DPE/DPE vapor alter proteins involved in maintaining skin integrity in primary skin keratinocytes. DPE vapor affects proteins associated with OXPHOS and cell migration in skin keratinocytes. Similar effects are observed upon DPE/DPE vapor treatment in 2D and 3D skin model. Vitamin E partially restores altered proteins in DPE/vapor exposed skin keratinocytes. Abstract: Background: Skin acts as a protective barrier against direct contact with pollutants but inhalation and systemic exposure have indirect effect on keratinocytes. Exposure to diesel exhaust has been linked to increased oxidative stress. Objective: To investigate global proteomic alterations in diesel particulate extract (DPE)/its vapor exposed skin keratinocytes. Methods: We employed Tandem Mass Tag (TMT)-based proteomics to study effect of DPE/DPE vapor on primary skin keratinocytes. Results: We observed an increased expression of oxidative stress response protein NRF2, upon chronic exposure of primary keratinocytes to DPE/its vapor which includes volatile components such as polycyclic aromatic hydrocarbons (PAHs). Mass spectrometry-based quantitative proteomics led to identification 4490 proteins of which 201 and 374 proteins were significantly dysregulated (≥1.5 fold, p ≤ 0.05) in each condition, respectively. Proteins involved in cellular processes such as cornification (cornifin A), wound healing (antileukoproteinase) and differentiation (suprabasin) were significantly downregulated in primary keratinocytes exposed to DPE/DPE vapor. These results were corroborated in 3D skin models chronically exposed to DPE/DPE vapor. Bioinformatics analyses indicate that DPE and its vapor affect distinct molecular processes in skin keratinocytes. Components of mitochondrial oxidative phosphorylation machinery were seen to be exclusively overexpressed upon chronic DPE vapor exposure. In addition, treatment with an antioxidant like vitamin E partially restores expression of proteins altered upon exposure to DPE/DPE vapor. Conclusions: Our study highlights distinct adverse effects of chronic exposure to DPE/DPE vapor on skin keratinocytes and the potential role of vitamin E in alleviating adverse effects of environmental pollution.